Progress in Hemodialysis - From Emergent Biotechnology to Clinical Practice 2011
DOI: 10.5772/21597
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Patients with ESRD Undergoing Hemodialysis

Abstract: Sleep has been identified as an essential human need; this is partly because of the metabolic activities that occur while the individual is sleeping. Normal sleep is divided into non-rapid eye movement (NREM) and rapid eye movement (REM) sleep. NREM sleep comprises 75% to 80% of total sleep time (TST), and is characterized by relatively quiescent brain activity and decreased metabolic rate (Carskadon & Dement, 2000). NREM sleep consists of four stages (S1-S4), with each stage leading to a progressively deeper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 102 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…It was determined that elderly patients were more likely to report poor quality of sleep. Similarly, studies by Yoshioka et al 5 and Tel et al 13 found that advanced age significantly affected patients experiencing sleep problems. This may also be due to age related changes in sleep, or due to increased prevalence of physical diseases, multiple drug use or lifestyle modification 5 .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…It was determined that elderly patients were more likely to report poor quality of sleep. Similarly, studies by Yoshioka et al 5 and Tel et al 13 found that advanced age significantly affected patients experiencing sleep problems. This may also be due to age related changes in sleep, or due to increased prevalence of physical diseases, multiple drug use or lifestyle modification 5 .…”
Section: Discussionmentioning
confidence: 77%
“…However, Unruh et al observed no difference in SQ by BMI 20 . An association between morning dialysis shift and poor SQ in HD population is reported in some studies 5,22 . We also found morning dialysis shift as an independent predictor of poor SQ.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Insomnia, restless legs syndrome (RLS), sleep apnea and excessive daytime sleepiness (EDS) are the most common sleep disorders among these patients (12). Poor sleep quality increases the risk of cardiovascular diseases and infections (13). According to the literature, poor sleep quality is associated with physical factors, such as underlying diseases (14), uremia (15), anemia (16) and metabolic changes induced by melatonin (17).…”
Section: Introductionmentioning
confidence: 99%